(449) Preconditions For Educational Planning شروط مسبقة للتخطيط التعليمي - El Koussy, A. A. (The Institute of National Planning, 2025)
This study examines the fundamental prerequisites required for effective educational planning as an essential component of comprehensive development planning. The study is based on the premise that educational planning effectiveness depends not only on the formulation of policies and objectives but also on the availability of institutional, economic, social, and statistical conditions that provide a scientific foundation for planning activities. The study explains that educational planning represents a systematic process aimed at aligning educational outputs with societal requirements, labor market needs, and broader economic and social development objectives. Therefore, successful planning requires accurate information regarding population size, demographic structure, population growth rates, labor force characteristics, and existing educational conditions. Furthermore, the study highlights the importance of statistical systems and information resources as essential tools for estimating future educational requirements and forecasting demand for educational services at different levels. Reliable and accurate information is considered critical for improving planning efficiency and ensuring rational allocation of financial and human resources. The study also addresses the role of educational institutions and governmental agencies in establishing an organizational environment supportive of planning processes. Particular emphasis is placed on coordination between educational authorities and development institutions in order to ensure consistency between educational policies and national development goals. In addition, the study emphasizes the necessity of establishing clearly defined educational objectives linked with broader governmental strategies and development plans. Such integration contributes to improving decision-making processes and enhancing the capacity of educational systems to respond to future developmental needs. The study concludes that successful educational planning requires the integration of statistical, institutional, economic, and human prerequisites within a comprehensive framework capable of supporting sustainable educational development and improving the efficiency of resource utilization.